Ekowisata Berbasis Komunitas dan Keberlanjutan Budaya: Peran Strategis Pemuda dan Perempuan dalam Gerakan Lingkungan di Pantai Liang, Maluku - Sunarti, Sunarti; Murwani, Prapti (Universitas Pattimura, 2022)
This article examines the strategic role of youth and women in the development of community-based ecotourism at Liang Beach, Maluku, as a form of grassroots social mobilization that integrates environmental advocacy and local cultural preservation. Employing a qualitative approach through participatory observation, in-depth interviews, and analysis of local documents, the study explores the dynamic social roles of local actors in ecotourism practices. Findings reveal that youth and women are not merely facilitators of tourism activities but act as change agents who construct ecotourism spaces grounded in cultural values and community ecology. Their involvement reflects resistance to the dominance of external actors and signals the emergence of a new collective identity rooted in social solidarity and environmental sustainability. The novelty of this study lies in positioning Eastern Indonesia as a peripheral yet significant locus of social knowledge production, and in reframing ecotourism as a locally driven social practice rather than solely an economic or institutional project. It advances sociological perspectives on environment, gender, and community by offering a contextual and participatory approach to understanding shifting power relations, symbolic resistance, and cultural identity reconstruction through ecotourism. These findings contribute to developing socially and ecologically just tourism models within broader social and political discourses.